2016
DOI: 10.1126/science.aad5978
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding proteins ZFP36L1 and ZFP36L2 promote cell quiescence

Abstract: Progression through the stages of lymphocyte development requires coordination of the cell cycle. Such coordination ensures genomic integrity while cells somatically rearrange their antigen receptor genes [in a process called variable-diversity-joining (VDJ) recombination] and, upon successful rearrangement, expands the pools of progenitor lymphocytes. Here we show that in developing B lymphocytes, the RNA-binding proteins (RBPs) ZFP36L1 and ZFP36L2 are critical for maintaining quiescence before precursor B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 152 publications
(150 citation statements)
references
References 51 publications
5
136
2
Order By: Relevance
“…Interestingly, in the same system the expression of GFP–TTP-AA was strongly anti-proliferative and reduced the viability of cells to 50% after 20h of doxycycline treatment (Figure 6B). This suggested a potential role for TTP in cell cycle regulation as proposed for the other two Zfp36 family members Zfp36l1 and Zfp36l2 (60). Analysis of apoptosis by 7-amino-actinomycin D (7-AAD) incorporation showed that induction of GFP–TTP-AA expression with doxycycline increased the number of apoptotic cells over time, whereas expression of GFP and GFP–TTP had no effect (Figure 6C).…”
Section: Resultsmentioning
confidence: 67%
“…Interestingly, in the same system the expression of GFP–TTP-AA was strongly anti-proliferative and reduced the viability of cells to 50% after 20h of doxycycline treatment (Figure 6B). This suggested a potential role for TTP in cell cycle regulation as proposed for the other two Zfp36 family members Zfp36l1 and Zfp36l2 (60). Analysis of apoptosis by 7-amino-actinomycin D (7-AAD) incorporation showed that induction of GFP–TTP-AA expression with doxycycline increased the number of apoptotic cells over time, whereas expression of GFP and GFP–TTP had no effect (Figure 6C).…”
Section: Resultsmentioning
confidence: 67%
“…Additional reporter gene assays indicate that ZFP36L1-dependent regulation requires a region containing conserved AU-rich elements in the 3′-UTR of Cyp7a1 mRNA. Indeed, previous studies have shown that Zfp36l1 functions to repress cytokine and cell-cycle mRNAs by binding to AU-rich sequences in their 3'-UTRs (13,27,31). However, a role for Zfp36l1 in regulating hepatic mRNAs in vivo, including those involved in lipid and bile acid metabolism, has not been reported.…”
Section: Discussionmentioning
confidence: 96%
“…Although at their inception CLIP techniques did not attend to background (Ule et al 2003(Ule et al , 2005Hafner et al 2010;Konig et al 2010), it has since been shown that significant background remains in CLIP experiments (Friedersdorf and Keene 2014) and that accounting for it greatly improves identification of binding sites ReyesHerrera et al 2015;Conway et al 2016;Galloway et al 2016;Holmqvist et al 2016;Van Nostrand et al 2016). However, it is not known whether this is due to improved signal-to-noise detection or whether the difference in enrichment represents quantitative differences in binding to various submotifs (Kishore et al 2011;Lambert et al 2015;Conway et al 2016).…”
Section: Discussionmentioning
confidence: 99%